PENGARUH LIVE STREAMING SHOPPING DAN AFFILIATE MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA APLIKASI TIKTOK SHOP ( Studi Kasus Mahasiswa UM Bengkulu Pengguna Aplikasi Tiktok di Kota Bengkulu ) - Izumi, Chalvina Firda; Nengsih, Mimi Kurnia (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
The title of this research is The Influence of Live Streaming Shopping and Affiliate Marketing on Product Purchasing Decisions on the Tiktok Shop Application (Case Study of Bengkulu Muhammadiyah University Students Using the Tiktok Application in Bengkulu City). This research is based on the importance of Affiliate Marketing for business companies. Several factors that influence Affiliate Marketing are Live Streaming Shopping and purchasing decisions. This research aims to determine the influence of live streaming shopping and affiliate marketing on product purchasing decisions on the TikTok Shop application. This type of research is quantitative research with a descriptive approach. The research population is all users of the TikTok Shop application. The total sample was 100 people, taken using accidental sampling technique. Data collection uses a questionnaire. The data analysis technique uses Multiple Linear Regression analysis. Partial test results show that live streaming shopping has a positive and significant effect on the purchasing decision. Simultaneous test results show that the live streaming shopping variable and the affiliate marketing variable together have a significant effect on purchasing decisions.  Keywords: live streaming shopping, affiliate marketing, purchasing decisions